THE CONTRIBUTION OF J. M. KEYNES TO THE ANALYSIS OF THE PSYCHOLOGICAL MOTIVES OF ECONOMIC BEHAVIOR - M. A. Kozlova (Vestnik MGIMO-Universiteta)
The article examines the contribution of John Maynard Keynes to the study of the psychological motives of economic behavior. The origins of the analysis of the psychological motives in economics before Keynes are reviewed. The relative importance of rational and irrational motives of economic behavior in the Keynesian theory is analyzed. It is shown that Keynes's analysis of the behavior of the economic agents under uncertainty and the lack of information contributed to the elaboration of the bounded rationality theory by Simon. The article also describes the input of Keynes to the formation of a new «Keynesian» model of human behavior, which implies the importance of expectations, taking into account the psychological and social factors of economic behavior. The main psychological tendencies in the actions of the consumers and investors described by Keynes (the basic psychological law, liquidity preference, the influence of the «market psychology» on the investor's decisions) and their relevance nowadays are examined. The article shows further development of the ideas of Keynes in the Akerlof and Shiller's theory of animal spirits and in the financial instability hypothesis of Minsky. It also gives a description of a confidence multiplier, introduced by Akerlof and Shiller, and shows how the cosumers' confidence can be measured nowadays. Besides, the article stresses that the study of the psychological motives of economic behavior, undertaken by Keynes, contributed to the development of such new disciplines at the interface between the economy and psychology as the economic psychology and behavioral economics.